Menakar Pemberdayaan Masyarakat Model Desa Konservasi (MDK) Pada Sekitar Kawasan Ksa/Kpa Kunyi dengan Metode Analytical Hierarchy Proscess (AHP): Menakar Pemberdayaan Masyarakat Model Desa Konservasi (MDK) Pada Sekitar Kawasan Ksa/Kpa Kunyi dengan Metode Analytical Hierarchy Proscess (AHP) - Andi Arafat (Jurnal Hutan dan Masyarakat, 2021)
ABSTRACT: Community well-being in conservation area management remains a challenge. The government has carried out community empowerment programs as stipulated in the Regulations of the Ministry of Environment and Forestry. Kunyi Village is a model conservation village directly adjacent to KPA / KSA Kunyi. One of the efforts made to empower communities around conservation areas is through the Conservation Village Model (MDK). Through the MDK, the development of the area around the forest conservation area is expected to take into account environmental, social and economic aspects. This research is important to see existing forms of empowerment and to formulate the direction of MDK's development. The research was conducted from May to October 2021. The data obtained was identified through community empowerment indicators. In addition, the driving and inhibiting factors were identified to determine the importance of each factor through a analysis hierarchy process (AHP). The results showed that there were several driving and inhibiting factors of empowerment seen from the aspects of knowledge, attitudes and skills produced. These factors will be strengthened through a strategy or plan of action. Keywords: Conservation, Conservation Village Model (MDK), Analysis Hierarchy Process (AHP)